On the conceptual evolution about black hole formation - Aranha, Rafael (Cadernos de Astronomia, 2023)
The intellectual development around the formation of black holes has a very rich history, as it does not only involve technical issues particular to the theory of general relativity. The full understanding of gravitational collapse both discusses various topics of relativistic astrophysics, as well as evidences the participation of many of the greatest physicists in the history of science. This article aims to address, in an introductory and conceptual way, the main characteristics of the formation of black holes, in a chronological line of initial rejection, followed by their inevitable acceptance.
Keywords: black holes; gravitational collapse; relativistic astrophysics; gravitation